Replacement of conventional steel rebar with bamboo reinforcement in concrete beams - Pathak K.K.; Jat D.K. (My University, 2025)
In this study, attempts have been made for the use of bamboo as reinforcement in place of conventional steel rebar. It includes selection of bamboo, comparison between physical and mechanical properties of bamboo and steel, bamboo specimen preparation (splitting, waterproofing, application of sand on specimen, stirrups preparation), casting of beams and testing thereof. Test results include ultimate load and crack pattern developed with different percentage of bamboo as reinforcement and their comparison with conventional steel reinforcement. In this study six beams were prepared, in which four beams have bamboo reinforcement of 1%, 2%, 3% and 4% to the cross section area of beams respectively, one beam with 1% steel rebar and one beam without reinforcement to compare their flexural behavior. It is observed that bamboo reinforcement enhances the flexural strength significantly due to which it can be considered as a replacement to steel in cost effective manner. © 2018 Associated Cement Companies Ltd. All rights reserved.